The Heart of Change: Acceptance and Intimacy Mediate Treatment Response in a Brief Couples Intervention - Hawrilenko, Matt (J Fam Psychol, 2015)
This study examined mediators of a brief couples intervention. Intimate safety, acceptance, and activation were examined in two roles: their contribution to marital satisfaction gains in the first two weeks after treatment (contemporaneous effects), and how early changes in the mediators influenced longer-term changes in marital satisfaction over two years of follow-up (lagged effects). Married couples (N = 215) were randomized to intervention or wait-list control and followed for two years. Latent change score models were used to examine contemporaneous and time-lagged mediation. A booster intervention in the second year was used for a replication study. Changes in intimate safety and acceptance were uniquely associated with contemporaneous treatment effects on relationship satisfaction in year one, but only acceptance was uniquely associated with contemporaneous effects in year two. With respect to lagged effects, early changes in acceptance partially mediated later changes in marital satisfaction in year one, whereas the same effect for intimate safety was marginally significant. These lagged paths were moderate in size and indirect effects were small. No lagged effects were significant in year two. Changes in activation were not significant as either a contemporaneous or lagged predictor of changes in relationship satisfaction. This study found moderate support for acceptance and more limited support for intimate safety as mediators of short and long-term treatment response, suggesting that these processes play an important role in sustaining marital health.